Zero Based Budgeting : An Important Tool (Trinity Journal of Management, IT & Media (TJMITM), 2016)
ZBB is an effective tool to maneuver organizations of better  allocation of their financial and non-financial resources. In  application, this method puts a requirement for each organization  to re-evaluate annually its activities from the zero ground. It  necessitate for an effective budget procedure is increasingly  apparent in business enterprises, so as to face the appareling  operating costs and declining growth rates. In this present era  of hectic competition, inflation technological advancement of  world wide, lofty costs of production and distribution & depleting  resources, no organization can be able to survive and flourish  unless it adopts an effective approach to budgeting system.  ZBB is a significant technique in which unneeded expenditures  are eradicate from the proposed budget. This paper, elaborate  the concept, definitions, budgeting process, decision units,  decision packages, benefits and lacunas of ZBB. ZBB presents  an opportunity for organizations to cut costs and improve  quantitative and qualitative aspects of operations.Despite  increasing popularity and interest, comprehensive ZBB cycles are  not a cost-effective option for most organi¬zations in either the  public or private sectors. However, ZBB components and theory  may be useful in specific sectors under specific circumstances. Although the economic envi¬ronment has driven renewed interest  in ZBB, more practical and less costly budgeting alternatives are  available that can meet organizational needs.
Keywords: Non-financial Resources; Budgeting; Decision Unit; Decision Packages; Inflation